2019
DOI: 10.1111/j.1740-9713.2019.01271.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Rise: Women Voters in India

Abstract: Women voters have shown increased participation and influence in India's elections since the first Lok Sabha – the lower house of parliament – was elected in the 1950s. Journalist Prannoy Roy and pollster Dorab R. Sopariwala explain the changes and the effects they are having on the country's democracy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Pakistan's electoral turnover at the individual level is also high with the share of Pakistani parliamentarians serving their first term in office ranging from a low of 41% in 2018 to 60% in 2008. These rates are similar to the rates found in many developing democracies (Roy and Sopariwala 2019; Sayari and Hasanov 2008). Incumbent politicians at all levels show weak commitment to democratic values and practices and have often abused their institutional powers to politically target and weaken political rivals and critics (Jalal 2017; Ullah 2013; Yadav 2021).…”
Section: Religion In Pakistani Politicssupporting
confidence: 85%
See 1 more Smart Citation
“…Pakistan's electoral turnover at the individual level is also high with the share of Pakistani parliamentarians serving their first term in office ranging from a low of 41% in 2018 to 60% in 2008. These rates are similar to the rates found in many developing democracies (Roy and Sopariwala 2019; Sayari and Hasanov 2008). Incumbent politicians at all levels show weak commitment to democratic values and practices and have often abused their institutional powers to politically target and weaken political rivals and critics (Jalal 2017; Ullah 2013; Yadav 2021).…”
Section: Religion In Pakistani Politicssupporting
confidence: 85%
“…For example, incumbent party activists may enact violence against rival party supporters during or between elections knowing the police forces will favor their party, and, tax agencies and security agencies may be used by incumbents to harass opposition party parliamentarians and their families (Mainwaring and Bizarro 2019; Haggard and Kaufmann 2016). Furthermore, developing country democracies tend to have significantly higher electoral turnover at the individual level than developed country democracies (Gouglas, Maddens, and Brans 2018; Roy and Sopariwala 2019; Sayari and Hasanov 2008). Thus, the chances of getting elected initially are lower and the chances that incumbents lose are higher.…”
Section: Religion In Pakistani Politicsmentioning
confidence: 99%
“…Errors in voter rolls may be particularly large in cities with high rates of in-migration (Janaagraha 2015, 2020) and rural areas with high rates of out-migration (Verma et al 2019). Researchers comparing voter rolls with India’s Population Census estimate high exclusion for certain demographic groups such as women (Roy and Sopariwala 2019) and Muslims (Shariff and Saifullah 2018). Given these findings, it is important for researchers and policymakers who rely on samples drawn from voter rolls to know the extent of errors in the voter rolls and to know how these errors bias any resulting sample drawn using voter rolls as a sampling frame.…”
Section: Introductionmentioning
confidence: 99%
“…Yet several studies have cast doubt on the completeness and accuracy of voter rolls in India in both urban (Janaagraha, 2015, 2020) and rural areas (Verma et al 2019). Other studies have compared the number of adults reported by the Indian Population Census and registered voters in voter rolls to highlight potential exclusion errors in voter rolls (Retnakumar 2009; Roy and Sopariwala 2019). Our article is the first direct comparison of voter rolls in India with independent listings of individuals in the same polling stations to estimate exclusion errors.…”
Section: Introductionmentioning
confidence: 99%